Factors Influencing Employee’s Well-Being and Job Performance: The Perspective of State-Owned Enterprise Employee - Muhammad Ihsan Mustika; Fanny Martdianty (Program Studi S3 Ilmu Manajemen, 2023)
State-Owned Enterprises (SOEs) play a crucial role in ensuring stability and control in Indonesia's economy, especially before and after the COVID-19 pandemic. The pandemic COVID-19 has accelerated the digitization of public and private sector activities in Indonesia and other countries. To adapt to the accelerated digitization caused by the pandemic, SOEs must continue to grow and develop to achieve their targets and goals. The intended goal of this study is to inquire into the impact of technostress, perceived organizational support (POS), total reward systems (TRS), and work-life balance (WLB) on job performance, as mediated by employee well-being (study of SOEs employee). This research employs a quantitative approach to investigate the direct and indirect impacts of the dependent variable through the utilization of the Structural Equation Modelling (SEM) technique. The study focuses on a sample of 263 respondents who are employees of State-Owned Enterprises (SOEs). This research highlights the role of perceived organizational support as a key driver of job performance mediated by employee well-being. The findings emphasize the significance of effectively engaging all generations, particularly Generation Y and Generation Z, within SOEs to strengthen job performance and accomplish organizational success. Furthermore, the study uncovers that employee well-being acts as a full mediator in constructing the connection between the variables under consideration and job performance. This finding emphasizes the importance for companies to continuously maintain perceived organizational support, ensuring that employees feel their well-being is being taken care of and their contributions are valued, especially for the younger generations (Generation Y and Z) who are the successors within the company.